Minimal clinically important differences in functional motor scores in adults with spinal muscular atrophy. (6th September 2020) - Stolte, B.; Bois, J.‐M.; Bolz, S.; Kizina, K.; Totzeck, A.; Schlag, M.; Kleinschnitz, C.; Hagenacker, T.
Abstract : Background and purpose: In patients with spinal muscular atrophy (SMA), functional disease scores are frequently used to evaluate the course of the disease and the efficacy of treatment. The aim of the present study was to propose minimal clinically important difference (MCID) values for motor scores in order to estimate the degree of change within a functional score that can be considered clinically meaningful. Methods: To estimate the MCID, distribution‐based approaches were used. For each assessment [Revised Upper Limb Module (RULM), Hammersmith Functional Motor Scale Expanded (HFMSE) and 6‐min walk test (6MWT)] and subgroup (SMA type 2, SMA type 3, ambulatory and non‐ambulatory), the following MCID values based on a cohort of 51 adults with SMA were calculated: standard error of measurement (SEm), one‐half of standard deviation (1/2 SD) and one‐third of standard deviation (1/3 SD) of patients' baseline scores. Results: For the overall cohort, the SEm, 1/2 SD and 1/3 SD MCID values were 2.9, 6.4 and 4.3 for the RULM and 4.3, 10.6 and 7.0 for the HFMSE, respectively. Subgroup analysis led to generally lower standard deviations and consecutively lower MCID values due to the significantly different motor functions of the groups. The respective MCID values for the 6MWT were 55.5 m, 71.1 m and 47.8 m. Conclusions: Our data provide MCID values for functional motor scores commonly used in adults with SMA in order to distinguish statistical effects from 'real' changes. A complementary systematic consensus process could help to further adjust the MCID values we propose.